Quel est le débit le plus fréquent d'un cours d'eau ? - Claire Lang-Delus; Didier François; Emmanuel Gille (Physio-Géo)
This paper takes an interest on the most frequent flow of a river, i.e. the modal flow. This variable is rarely used in hydrology whereas it could give interesting information about catchments behaviors. In this work we compare several methods of modal flow estimates. The modal flow values are then compared to widely use characteristic flows. We show for example that the modal flow is far from the mean flow which is one of the most common values used to characterize the average behavior of rivers.